Literature Review: Human Resource Management Strategy in Improving Employee Performance of Profit-Oriented Organizations - Alice Erni Husein; Wasiman Wasiman (Green Publisher Indonesia, 2026)
This literature review investigates the role of Human Resources Management (HRM) as a strategic factor in improving employee performance with regards of profit-oriented organizations. By analyzing 35 selected academic articles that published from 2021 to 2025, the study identifies several core HRM approaches that enhancing employee performance. Key focuses included work discipline, motivation, career development, communication, and organization culture respectively. Findings indicates that strategic HRM as far as the aforementioned key focuses are concerned, significantly improves the resilience of organization in addressing global concerns. The report advocated for centered around humanity, empirical data-driven approach to establish an economically feasible HRM framework for profit-oriented organizations. Research gaps are found, hence future investigation being recommended too.